Clinical Pharmacological Approach To Rational Drug Treatment Of Chronic Heart Failure (Texas Journal of Medical Science, 2025)
The clinical pharmacological approach to the rational drug treatment of chronic heart failure (CHF) focuses on optimizing therapeutic strategies to improve patient outcomes. This article examines the pharmacological classes of drugs used in CHF management, including angiotensin-converting enzyme (ACE) inhibitors, beta-blockers, diuretics, aldosterone antagonists, and novel agents. The mechanisms of action, indications, contraindications, and potential adverse effects of these drugs are analyzed. Special emphasis is placed on the importance of individualized treatment, drug interactions, and evidence-based guidelines. Advances in pharmacotherapy and personalized medicine approaches for enhancing the efficacy and safety of CHF treatment are also discussed.